Search for W′ bosons decaying to a top and a bottom quark at √s=13TeV in the hadronic final state; Physics Letters B; Vol. 820 - Sirunyan А. М.; Tumasyan A. R.; Adam W. Wolfgang; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich; Sukhikh L. G. Leonid Grigorievich (2021, 2021)
Title screen